2002
DOI: 10.3748/wjg.v8.i2.267
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopic screening and follow-up for colorectal cancer in the elderly

Abstract: AIM: To improve the prevention and treatment of senile patients with colorectal cancer by evaluating the importance of colonoscopy in clinical screening and follow-up.METHODS: Clinical screening of colonoscopy was performed for 2196 patients aged 60-90 years old according to the protocol,and 1740 of them (79.2%) were followed-up. RESULTS:Colorectal cancer was found in 52 patients, and the detectable rate was 2.4%. Among them, 19 were diagnosed as early colorectal cancer, accounting for 36.5% of the detected co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Eight studies were obtained that reported on adenoma detection rates (11,15,32,35,39,40,60,62). The characteristics of the study populations varied across the reports.…”
Section: Adenoma Detection Rates -Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies were obtained that reported on adenoma detection rates (11,15,32,35,39,40,60,62). The characteristics of the study populations varied across the reports.…”
Section: Adenoma Detection Rates -Literature Search Resultsmentioning
confidence: 99%
“…No studies were obtained that provided data on patient assessment, infection control, monitoring during and after administration of conscious sedation, or resuscitation capability. However, the following data were provided in specific papers: perforation rate -eight papers (12,(17)(18)(19)(20)(21)60,61), bleeding -nine papers (12,13,18,(22)(23)(24)(25)60,61), cecal intubation rates -14 papers (11)(12)(13)(14)(15)17,18,(26)(27)(28)(29)(30)(31)60), average colonoscope withdrawal times -five papers (18,30,(32)(33)(34), adenoma detection -eight papers (11,15,32,35,39,40,60,62), CRC miss rates -seven papers (15,35,36,…”
Section: Literature Searchmentioning
confidence: 99%
“…Colonoscopy is an important tool for the diagnosis and surveillance of colonic neoplasms and for the treatment of appropriately selected lesions [14]. Numerous publications have documented the benefits of colonoscopy [2,11,12,16,22,23], however, only a few have discussed its value in the elderly [5,17,18,24].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous longitudinal feasibility studies. For example, a study from China followed 2,196 asymptomatic elderly patients screened with frequent colonoscopies over 6 yr (27); during this period, 52 cancers and 5,801 adenomas were found. The complication rate (0.05%) and cecal intubation rate (98.9%) were quite acceptable.…”
Section: Discussionmentioning
confidence: 99%